(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Can we regulate a significant segment of cross-border relations that arise in cyberspace with the available legal tools, or is it appropriate to talk about the formation of a new normative body of cyberlaw? The purpose of this article is an attempt to answer this question through the prism of the mechanism for regulating cross-border private law relations that are the subject of international private law. Due to the nature and complexity of the “foreign element”, cross-border private law relations, in terms of their regulation, are as close as possible to those that arise in connection with the scaling of cyberspace.